Knowledge and Skill Chains in Engineering and Manufacturing Information Infrastructure in the Era of Global Communications. - Arai, Eiji; Kimura, Fumihiko; Shirase, Keiichi (IFIP Advances in Information and Communication Technology,, 2005)
This book explores knowledge and skill chains in engineering and manufacturing in the age of global communications. Information infrastructure involves a range of activities from product planning, engineering, and manufacturing trough transportation, marketing, and repair/upgrade to returns and recycling/disposal. Distinct from the traditional engineering database, life-cycle support information has its own characteristic requirements, -- flexible extensibility, distributed architecture, multiple viewpoints, long-time archiving, and product usage information. Several authors address the architecture of the information infrastructure, its services and its requirements. Other papers focus on the knowledge and skill chains that develop in a variety of situations: the supply chain, the factory floor, the man-system interaction, etc. For each of these, state-of-the-art and state-of-research scenarios for various industrial sectors address both engineering and operations requirements in the current socio-economic environment. The editors' introductory essay provides a unifying framework for these expert and wide-ranging studies in the modeling, design and development, and applications of information infrastructures in global enterprises and business networks. This book will be essential reading and reference for all researchers, engineers and managers concerned with business models of, and IT support for virtual enterprises and manufacturing networks. It presents a comprehensive text on information infrastructure for manufacturing and enterprise integration, modeling methodologies, and applications of information and telecommunication technologies.